PEMBELAJARAN STATISTIKA INFERENSI BERBASIS CASE METHOD DAN TEAM-BASED PROJECT TERINTEGRASI NILAI PANTANG LARANG SUKU MELAYU UNTUK MENGUKUR KEMAMPUAN BERPIKIR KRITIS MAHASISWA - Prihatin Ningsih Sagala; Eri Widyawati; Puteri Atikah (MES: Journal of Mathematics Education and Science, 2026)
This study aims to analyze the validity of a case-method and team-based project-based assessment instrument for Inferential Statistics, integrating Malay values of "Pantai Larang" (Prohibition of the Malay Tribe) in measuring students' critical thinking skills. The study was conducted in the Mathematics Education Study Program, Faculty of Mathematics and Natural Sciences, Medan State University, during the even semester of the 2024/2025 academic year, using a research and development (R&D) approach. The validation process was conducted by four expert validators who assessed aspects of content, construction, language, and cultural contextual appropriateness. Data were analyzed descriptively by calculating a validity percentage. The validation results showed an average validity level of 73.25%, categorized as valid. This instrument was deemed appropriate for measuring students' critical thinking skills contextually, by combining active learning methods with local cultural values. These findings demonstrate that the integration of Malay cultural values in educational assessment can enhance the relevance, character, and meaning of learning. Therefore, the developed instrument is suitable for measuring students' critical thinking skills in Inferential Statistics learning based on character and local culture.